2022
DOI: 10.3390/molecules27144527
|View full text |Cite
|
Sign up to set email alerts
|

Speculation on How RIC-3 and Other Chaperones Facilitate α7 Nicotinic Receptor Folding and Assembly

Abstract: The process of how multimeric transmembrane proteins fold and assemble in the endoplasmic reticulum is not well understood. The alpha7 nicotinic receptor (α7 nAChR) is a good model for multimeric protein assembly since it has at least two independent and specialized chaperones: Resistance to Inhibitors of Cholinesterase 3 (RIC-3) and Nicotinic Acetylcholine Receptor Regulator (NACHO). Recent cryo-EM and NMR data revealed structural features of α7 nAChRs. A ser-ala-pro (SAP) motif precedes a structurally import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…If the misfolded proteins are α7, then this implicates a direct role for RIC3 in α7 folding as suggested by [ 17 ]. Given the disordered nature of RIC3, the localization of the exact interaction domain has proven to be challenging [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the misfolded proteins are α7, then this implicates a direct role for RIC3 in α7 folding as suggested by [ 17 ]. Given the disordered nature of RIC3, the localization of the exact interaction domain has proven to be challenging [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which RIC3 promotes α7 nAChR assembly is unknown [ 41 ] although a direct interaction is expected as α7 co-precipitates with RIC3 [ 20 , 42 ]. Wang et al suggested that each RIC3 protein associates with a single folded α7 subunit [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noviello et al (2021) using cryo-EM identified the conformational structures of the human α7 nAChRs and a C-terminal substructure involved in gating they called the "latch" [10]. Together with TM4, the "latch" may play an important role in RIC3 actions [10,19]. There is a highly conserved ser-ala-pro (SAP) motif located between TM4 and the "latch", suggesting that the SAP motif may have important effects on the folding and function of α7 nAChRs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Together with TM4, the "latch" may play an important role in RIC3 actions [10,19]. There is a highly conserved ser-ala-pro (SAP) motif located between TM4 and the "latch", suggesting that the SAP motif may have important effects on the folding and function of α7 nAChRs [19]. Noviello et al also proposed the ICD has a higher proportion of disordered regions than the ECD and TMDs [10].…”
Section: Introductionmentioning
confidence: 99%